Therapeutic project of crack and alcohol users attended in a psychosocial care center - Eliany Nazaré Oliveira; Maria Mazane Gomes Santana; Sara Cordeiro Eloia; Paulo César de Almeida; Tamires Alexandre Felix; Francisco Rosemiro Guimarães Ximenes Neto (Rev Rene)
Objective: to analyze the therapeutic project of crack and alcohol users attended at a psychosocial care center for alcohol and other drugs. Methods: documentary study that analyzed 567 medical records, in which 291 brought crack as the main complaint of biopsychosocial damages for users and 276 for alcohol. Results: the activities of reception, waiting room and home visit stood out in users’ therapeutic projects as well as in nursing and medical consultations. In most of the medical records one found pharmacological treatment by users and that complementary laboratory exams had not been requested. Conclusion: it is relevant to know the characteristics of the therapeutic project for the improvement of treatment strategies.